2022
DOI: 10.3390/ijms231911573
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Salt Stress Response Analysis of the bZIP Transcription Factor Family in Sugar Beet

Abstract: As one of the largest transcription factor families in plants, bZIP transcription factors play important regulatory roles in different biological processes, especially in the process of stress response. Salt stress inhibits the growth and yield of sugar beet. However, bZIP-related studies in sugar beet (Beta vulgaris L.) have not been reported. This study aimed to identify the bZIP transcription factors in sugar beet and analyze their biological functions and response patterns to salt stress. Using bioinformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Until now, many bZIP genes involved in salt stress responses have been characterized in various plant species. Gong et al identified 48 bZIP genes in the genome of sugar beet ( Beta vulgaris L.) and analyzed their biological functions and response patterns to salt stress [ 43 ]. Chai et al revealed that the overexpression of a soybean bZIP gene GmbZIP152 can enhance the tolerance to salt, drought, and heavy metal stresses in Arabidopsis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, many bZIP genes involved in salt stress responses have been characterized in various plant species. Gong et al identified 48 bZIP genes in the genome of sugar beet ( Beta vulgaris L.) and analyzed their biological functions and response patterns to salt stress [ 43 ]. Chai et al revealed that the overexpression of a soybean bZIP gene GmbZIP152 can enhance the tolerance to salt, drought, and heavy metal stresses in Arabidopsis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our functional prediction according to GO categories showed that the target genes were significantly enriched in molecular functions, including DNA-binding TF activity, TF binding, L-alanine transmembrane transporter activity, arginine transmembrane transporter activity, and gamma-aminobutyric acid transmembrane transporter activity. As mentioned above, genes involved in DNA-binding TF activity and TF binding have shown vital roles in regulating stress tolerance in plants [ 42 , 43 , 44 , 45 ]. Meanwhile, according to Zhou et al [ 56 ], miRNAs can also be involved in stress tolerance by regulating target genes that control transmembrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the genome of industrial diploid sugar beet (2n = 18 chromosomes) was sequenced, accelerating sugar beet breeding for tolerances and resistances against abiotic or biotic stresses [35]. So far, the structure and function of the BvbZIP and BvWRKY family, as well as their expression pattern under salt stress, have been genome-wide analyzed for sugar beet [42,43]. However, information about Q-type C2H2-ZFPs in sugar beet remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the molecular mechanisms of plant salt tolerance has scientific importance and practical significance (Liang et al, 2023). To reveal these mechanisms, extensive studies have been conducted to identify and characterize numerous genes and proteins associated with salt tolerance, such as LRX3/4/5 proteins, CCCH-type zinc finger proteins, LncRNA973, AtbZIP17, etc (Zhang et al, 2019;Medina et al, 2020;Zhao et al, 2021;Gong et al, 2022). Among them, transcription factors and their regulatory functions have been demonstrated to have a crucial impact on plant environmental adaptation (Li et al, 2022).…”
mentioning
confidence: 99%